New Hide Beetle (Dermestes maculatus) Recorded On Salted Dry Fishes from Pakistan - Hina Manzoor; M. Arshad Azmi (Journal of Basic & Applied Sciences, 2018)
There are many species which cause infestation in many ways. For estimation of infestation a laboratory work has started, during experiments a new species of Dermestes maculatus has been observed on dry salted fishes at Karachi coast.